One year of general practice during the COVID-19 pandemic – presentation and evaluation of digital medical education - van der Keylen, Piet; Zeschick, Nikoletta; Langer, Anna-Lena; Kühlein, Thomas; Roos, Marco (GMS Journal for Medical Education, 2022)
Background and teaching situation: The SARS-CoV-2 pandemic had a substantial didactic impact on medical teaching. In Erlangen, the lecture “General Practice” was offered asynchronously and digitally in an inverted-classroom concept. Contents were available via a learning platform. The lecture was presented using annotated videos, consolidation materials and control questions. A forum encouraged for discussions and feedback and collected in-depth aspects for a case-based video consultation. The aim of this work is to evaluate and critically examine the digital teaching concept during the SARS-CoV-2 pandemic.Methodology: Two semester cohorts evaluated the lecture. Overall impression of the lecture, didactic elements, suitability and the desired future lecture format were surveyed quantitatively. Free text answers were evaluated by means of qualitative content synthesis.Results: In terms of overall impression, the students (=199) rated the lecture on average as (=1.41, =.57). Digital methods were perceived as suitable for supporting self-study, and digital usage was rated as unproblematically (=1.18, =.50). Desired future teaching formats were blended learning concepts (79.4%). Organisation, structure and content presentation were highly appreciated. The time for completing the course was perceived critically. The students urged for more practical and consolidating lecture work.Discussion and implications: The results illustrate high acceptance of digital teaching and underline the demand for future blended learning concepts. It is particularly important to better consider the students’ time investment and practical relevance of digital self-learning mechanisms.